Alexander of Hales and the distinction between Revealed Theology and Speculative Sciences: First Philosophy, Physics and Maths (Circe de clásicos y modernos, 2024)
The present text is the complete translation from Latin into Spanish of the Alexander of Hales’ Sum of the Theology (lib. I, tr. int., q. I, ch. I-IV). There he explains the main epistemic difference between Sacred Theology, rational Theology or First Philosophy, and the sciences of Physics and Maths. Then, Sacred Theology is separated from the other speculative sciences under a guiding criterion: Revealed Science is guided by the grace of God, while the other sciences are guided without grace and by the forces of reason alone. On this distinction, the terms Sacred Theology and Sacred Doctrine are then identified, without neglecting the need to harmonize the theological tradition with the advance of Latin Aristotelianism at the beginning of the 13th century.
Keywords: Alexander of Hales; Sacred Theology; First Philosophy; Speculative Sciences; Holy Scriptures